2004
DOI: 10.1128/jvi.78.14.7518-7522.2004
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for Natural Transmission of Small-Ruminant Lentiviruses of Subtype A4 from Goats to Sheep and Vice Versa

Abstract: Small-ruminant lentiviruses (SRLV), which include the caprine arthritis-encephalitis and the maedi-visna virus, cause persistent inflammatory infections in goats and sheep. SRLV are mainly transmitted from mother to offspring through milk. Transmission after prolonged contact between adult animals has also been observed. The observation that certain SRLV subtypes are found in both goats and sheep suggests that interspecies transmission has occurred on several occasions in the past. We investigated seropositive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 20 publications
2
56
0
9
Order By: Relevance
“…Interspecies transmission occurs in the field, as suggested by the detection of some SRLV subtypes in both sheep and goats (16,28,29,38). Recently, direct evidence was found proving that, in mixed flocks of sheep and goats, the SRLV subtypes A4 (32) and B1 (26) do indeed jump the species barrier. In view of these results, we reasoned that double infection may also occur in SRLV-infected goats and sheep.…”
mentioning
confidence: 95%
“…Interspecies transmission occurs in the field, as suggested by the detection of some SRLV subtypes in both sheep and goats (16,28,29,38). Recently, direct evidence was found proving that, in mixed flocks of sheep and goats, the SRLV subtypes A4 (32) and B1 (26) do indeed jump the species barrier. In view of these results, we reasoned that double infection may also occur in SRLV-infected goats and sheep.…”
mentioning
confidence: 95%
“…The MVV prototypical strains such as strain K1514, EV-1, and SA-OMVV from sheep and the CAEV strain Cork-CAEV isolated from goat (L'Homme et al 2011) were originally viewed as distinct viral species restricted to respective host animal species. As more SRLV sequences had become available for phylogenetic analyses, it became evident that SRLVs can cross the species barrier and can be transmitted from sheep to goats under favourable conditions (Shah et al 2004b;Pisoni et al 2005).…”
mentioning
confidence: 99%
“…5 In addition, viral strain typing has recently found that some goats contain ovine progressive pneumonia or maedi-like and visnalike viruses and that some sheep contain caprine arthritis encephalitis-like viruses. 12,62,63,66,68,73,74 Furthermore, because sheep and goats often cohabitate, eradication efforts have been focused on eliminating SRLVs in general. Persistently infected animals are a potential reservoir for transmission; therefore, highly specific and sensitive diagnostic tests are required for early detection and separation or culling of both infected sheep and goats.…”
Section: Transmission Sourcesmentioning
confidence: 99%